2012
DOI: 10.1557/jmr.2012.275
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on crystallization behavior, phase stability, and binding energy in pure and Cr-doped TiO2 nanotubes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…6b), anatase and rutile were first observed at 500°C, which is 100°C lower for anatase and 200°C lower for rutile than observed in the non-implanted material. These results are consistent with previously reported observations of non-implanted and Cr ion-implanted anodized TiO 2 nanotubes whereby Cr ion implantation lowered the crystallization temperature of anatase from 600 to 400°C and rutile from 600 to 500°C [14]. The observations are consistent with V ions entering the TiO 2 crystal structure [39], through the implanted ions occupying the Ti sub-lattice substitutionally, rather than interstitial positions.…”
Section: Effect Of Ion Implantation On Phase Transitionssupporting
confidence: 92%
See 1 more Smart Citation
“…6b), anatase and rutile were first observed at 500°C, which is 100°C lower for anatase and 200°C lower for rutile than observed in the non-implanted material. These results are consistent with previously reported observations of non-implanted and Cr ion-implanted anodized TiO 2 nanotubes whereby Cr ion implantation lowered the crystallization temperature of anatase from 600 to 400°C and rutile from 600 to 500°C [14]. The observations are consistent with V ions entering the TiO 2 crystal structure [39], through the implanted ions occupying the Ti sub-lattice substitutionally, rather than interstitial positions.…”
Section: Effect Of Ion Implantation On Phase Transitionssupporting
confidence: 92%
“…However, Chuangchote et al [12] claimed that TiO 2 nanofiber photocatalysts reported lower activity when both rutile and anatase phases were present. TiO 2 is an n-type semiconductor with a 3.0-3.2 eV band gap (E g ) [13][14][15]. It is activated by UV irradiation, about 4 % of natural solar light, which is one of the major factors limiting the efficiency of the TiO 2 photocatalysis [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Silica can inhibit the formation rutile by impeding direct contact between TiO 2 particle with forming the Ti-O-Si binding [8]. The same phenomenon was also observed on Cr-doped nano-titania in argon [31] where rutile phase is dominant after temperature above 900°C. The use of SiO 2 for TiO 2 matrix of 50% will reduce the anatase phases and forming amorphous TiO 2 -SiO 2 .…”
Section: Photocatalysissupporting
confidence: 55%
“…On the other hand, samples calcined at 600-700°C have grains separated clearly and they are quite similar although the grains in sample C are more homogeneous than samples D and E. At higher than 600°C, the presence of silica cannot prevent the growth of rutile phase. This is contrast with Cr-doping titania where rutile phase in the sample is around 5 wt% even the calcination temperature has reached 700°C [31]. Based on the Scherrer equation [35], the particle size of samples can be calculated by measuring the full half width maximum (FHWM).…”
Section: Microstructure Of Samplesmentioning
confidence: 99%
“…Chromium has been reported as an effective doping metal to modify TiO 2 for enhancing its photocatalytic activity [12][13][14][15]. Recent theoretical calculations showed that 3d transition metals have good potential as a substitutional dopant for TiO 2 because of their ability to induce significant spin polarization and reduce the energy gap of rutile by forming intermediate bands with adequate curvatures and density of states [16][17][18][19]. Different methods were used to prepare chromium-doped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%